The Value of Understanding Students' Prior Writing Experience in Teaching Undergraduate Science Writing - Clarke, Jumani (Critical Studies in Teaching and Learning, 2023)
How should undergraduate science students' writing be understood when it does not meet the conventions of scientific writing? Studies have shown that the writing that students produce in their course work on tasks that imitate authentic scientific writing practices often do not match the tone, vocabulary and grammatical choices made by professional scientists. However, from the perspective of looking at the students' word and grammar choices alone, it is not easy to understand why students make their particular and varied word and grammar choices and how those choices can be related to their understanding of the goals and discourses that are typical of science practices. Studying the writing of four first year earth and geographical sciences students on a science faculty's alternative access program, from an assignment in a course that introduced them to the research article, it seems that the students persist with the social purposes of their various school writing practices in attempting their new university writing tasks. It is this variety in the social purposes of the writing that the students continue to draw on in university that can explain some of the ways in which student writing does not meet even the broadest writing conventions of the discourses of science. Yet it seems that some of the social purposes and the related writing practices of some students can help them transition their writing more easily into a form that has the usual characteristics of a typical science genre. Therefore, understanding the social purposes that students bring with them can be crucial to successfully introducing them to the discourses of science and showing them how the social purposes of scientific practice can be served in a genre such as the research article.